Obtenção, caracterização e utilização de um compósito com matriz de resina poliéster e carga de fibras de sisal - Martins Neto, José Antônio (2016)
The constant search for sustainable alternatives has earned great effort of researchers in research and obtaining new materials, encouraging the rise of eco-friendly productive development and providing simple and practical solutions to economic profitability. In this sense, the use of materials derived from natural renewable sources, vegetables, has great potential applicability to sustainable development. As alternative materials plant fibers can be applied to production of a range of composite materials easing the use of materials derived from non-renewable this thesis were sisal mats used for achieving a composite matrix having as one orthophthalic polyester resin. The webs were subjected to surface treatment in boiling water for 15 minutes. The webs of sisal fibers used were, respectively, 5%, 10% and 15% of the composite weight. The composite was obtained and characterized mechanically and thermally to the chosen formulations. several plates of the composite to obtain the body of evidence for the characterization tests complying with the relevant rules were made. The obtained composites showed strength tensile and bending lower than the array, so it can be used where are required low load requests. The most significant result of the composite studied given to the impact energy absorption, far superior to the matrix used. Other properties were highlighted in oil absorption, and density. It proved the feasibility of obtaining the composite for the three formulations studied C5, C10 and C15 being the most feasible to C10. To demonstrate the feasibility of using composite were made a wall clock, a bench, a chair and a shelf, low mechanical stress structures. It was concluded that the sisal rugs exercised the load function in the composite.